Analisis Pengaruh Brand Switching Behavior Untuk Keputusan Pembelian Produk Hand Phone Di Kota Prabumulih - Samron Akhiri; Romsa Endrekson (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The development of increasingly modern technology makes industrial companies try to meet human needs by creating a product that can provide convenience in communicating. Currently, mobile phones are not only owned by the upper middle class but also the lower middle class people can own a mobile phone because the price is quite affordable for certain series. This study aims to determine the effect of brand switching behavior for the purchase of mobile phone products in Prabumulih City on mobile phone users in Prabumulih City. In order for this research to be focused, directed and not widespread, the authors limit the research to the effect of product attributes, prices, promotions and product inventories on mobile phones which are focused on mobile phone users in Prabumulih City. This research was conducted in Prabumulih City. Furthermore, the stages of the research method start from determining the design and type of research, the type of research data is quantitative, primary data sources using interviews and questionnaires using a Likert scale. The sample used in this study were mobile phone consumers with a total sample of 96 respondents. The research was conducted using the Non-Probability Sampling technique with a purposive sampling approach, namely taking samples from the population based on certain criteria. The data analysis method used is classical assumption analysis consisting of normality test, heteroscedasticity test, multicollinearity, correlation test, multiple linear regression, and hypothesis testing including t test, F test and coefficient of determination (R2). From the output model summary, the determination table above gives an Adjusted R Square of 0.843. This shows that the variable Extrinsic Factor (X1) and Intrinsic Factor (X2) simultaneously the percentage of the contribution of the influence of the independent variable has an influence on the dependent variable (purchase decision), the independent variable (Extrinsic Factors and Intrinsic Factors) is able to explain 84.3% of the variables dependent (purchase decision), while the remaining 15.7% is influenced or explained by other variables not examined in this study, such as promotion, product quality and others that may be able to complete this research. Keywords: Brand Switching Behavior and Purchase Decision